Analisis Trend Manajemen Humas Pendidikan Islam di Pondok Pesantren Nurul Jadid - Misbahul Arifin; Durrotul Masruroh (CV Edujavare Publishing, 2025)
This study focuses on analyzing the trends of public relations (PR) management in Islamic education at Nurul Jadid Islamic Boarding School, aiming to explore how communication strategies, the use of digital media, and social relations with communities and alumni are developed to strengthen the institution’s image. Employing a qualitative case study approach, data were collected through in-depth interviews, direct observations, and document analysis within the context of Nurul Jadid Islamic Boarding School, located on KH. Zaini Mun’im Street, Karanganyar, Paiton, Probolinggo. The collected data were analyzed descriptively and analytically to identify key patterns that illustrate the PR practices at the pesantren. The findings reveal that the institution’s PR management has transformed through three crucial aspects: strengthening transparent and responsive communication strategies, utilizing digital media such as Instagram, YouTube, and the official website as institutional branding tools, and building social networks with communities and alumni to reinforce legitimacy. However, limited human resources, uneven digital skills, and restricted financial support remain the main challenges. The implication of this study highlights that developing PR in pesantren during the digital era requires not only technological innovation but also internal capacity building and external collaboration, providing valuable insights for enhancing Islamic educational PR strategies in similar institutions.